(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2021)
Microorganisms play an integral role in detoxification and removal of toxic compounds from the environment. Aniline is the simplest aromatic amine, consisting of a phenyl group attached to an amino group that is used as herbicide to control weeds. Aniline is detrimental to both environment and health. In this research, six previously isolated bacteria (isolate A-F) were screened on Bushnell Hass media for their potential to grow and utilize aniline as a sole carbon source. Isolate A (Pseudomonas sp.) was found to tolerate and grow best with aniline sole source of carbon. Optimum conditions for aniline degradation by this isolate were found to be pH 6.0, temperature between 30 and 37 Â°C, inoculums size of 600 Î¼L, aniline concentration of 200 mg/L and incubation time of 96 h. The capacity of this isolate to reduce toxic aniline to less toxic form is novel and makes the bacterium important instrument for bioremediation of this pollutant.